Testicular biometry and semen quality is not altered by the process of fine needle aspiration in crossbred bulls - RAJAK, S K; KUMARESAN, A; GAURAV, M K; ASLAM, M K MUHAMMAD; MOHANTY, T K; PRASAD, SHIV; CHAKRAVARTY, A K; VENKATASUBRAMANIAN, V (The Indian Journal of Animal Sciences, 2013)
Testicular fine needle aspiration cytology (FNAC) is widely being used in humans to evaluate the functional testicularmechanism, but its application is very limited in animals especially breeding bulls. This preliminary study was conducted to assess the effect of testicular fine needle aspiration (FNA) technique on testicular biometry and seminal characteristics in Karan Fries crossbred bulls. Eight bulls within the age range of 4–6 years were utilized for study. Before and after fine needle aspiration, testicular parameters were measured and seminal quality was assessed as per standard protocols. There was no significant difference observed in scrotal circumference and testicular length before and after the treatment. The testicular width was 6.59±0.32 and 7.08±0.27 during pre- and post- aspiration, while the corresponding values for testicular mass were 355.77±39.20 and 427±28.75, respectively. There was no significant changes observed in ejaculate volume, mass activity and individual motility in bulls during pre-FNA and post-FNA period. Similarly, the percentageof live spermatozoa, membrane intact spermatozoa and acrosome intact spermatozoa did not differ significantly between pre-FNA and post-FNA period. These results indicated that testicular fine needle aspiration technique can be used as a routine diagnostic method to detect sub-fertility and infertility in crossbred bulls without affecting their reproductive health